2005
DOI: 10.1007/s00280-004-0960-5
|View full text |Cite
|
Sign up to set email alerts
|

HERG K+ channel expression-related chemosensitivity in cancer cells and its modulation by erythromycin

Abstract: HERG expression levels and chemosensitivity were positively correlated for vincristine, paclitaxel, and hydroxy-camptothecin. Erythromycin was active as a modulator. These results suggest that HERG may serve as a molecular marker and modulating target for individualized cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 21 publications
2
50
1
1
Order By: Relevance
“…Chen et al (28) reported that A549 cells expressing low levels of HERG were less sensitive than HT-29 cells expressing high levels of HERG to vincristine, paclitaxel and hydroxy-camptothecin. The chemosensitivities of HERG-transfected A549 cells to vincristine, paclitaxel and hydroxy-camptothecin were significantly increased, compared to parent A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (28) reported that A549 cells expressing low levels of HERG were less sensitive than HT-29 cells expressing high levels of HERG to vincristine, paclitaxel and hydroxy-camptothecin. The chemosensitivities of HERG-transfected A549 cells to vincristine, paclitaxel and hydroxy-camptothecin were significantly increased, compared to parent A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The human ether-a-go-go related gene (HERG) that encodes a delayed rectifier K + channel was shown to promote H 2 O 2 -induced apoptosis in a variety of tumor cells expressing this channel, in direct contrast to cells that lacked HERG expression [51]. Additionally, cell lines with high HERG potassium channel expression have been shown to be more sensitive to chemotherapeutic drugs than cells with a lower HERG expression [52]. Over-expression of HERG in low expressing cells resulted in an increase in sensitivity to drug treatment, again suggesting that potassium channels can be major players for the control and/or activation of apoptosis.…”
Section: Potassium Channels In Apoptosismentioning
confidence: 99%
“…Osteogenic Sarcoma ↑E2F-1 Transfection No change Sensitive [30] E2F-1(transcription factor) cyclin B1 levels and cdc2 kinase activity becoming sensitive to paclitaxel A549 Lung ↑HERG Transfection 0.875 0.039 [31] Potassium Channel, mechanism of paclitaxel sensitivity unknown SH-EP Neuroblastoma ↑MYCN Transfection 0.94 0.51 [32] Mechanism of paclitaxel sensitivity not studied [33] ↓BRCA1 leads to transcriptional modifications of the JNK pathway ↑JNK1 ↓JNK2 MCF-10A…”
Section: Genetic Modifications Which Induce the Inverse Cisplatin/pacmentioning
confidence: 99%